Isolation of new straight chain compounds from acacia nilotica - Chaubal, Rohini; Tambe, Amruta; Biswas, Sujata; Rojatkar, Supada; Deshpande, Vishnu; Deshpande, Nirinala (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2006)
A novel diester, pentacosane dioic acid dihexadecyl ester 1 has been isolated for the first time from n-hexane soxhlet extract of Acacia nilotica. Saponification of the diester reveals the presence of an alcohol, hexadecanol and pentacosane dioic acid. The structures of both the compounds are confirmed by GCMS analysis. Saponification of pet-ether extract of Acacia nilotica has been carried out. Unsaponiflable matter is further purified by column chromatography followed by repeated mixed solvent crystallization to afford heptacosan-1,2,3-triol 2.
Keywords: Acacia nilotica; diester; pentacosane dioic acid; saponification

In vitro antitubercular screening and in silico study of germacradienolide from blainvillea latifolia - Honmore, Varsha; Kalyankar, Vidya; Natu, Arun; Khedkar, Vijay; Sarkar, Dhiman; Rojatkar, Supada (Asian Journal of Chemistry, 2021)
Bioassay-guided isolation from acetone extract of Blainvillea latifolia yielded one compound. The acetone extract, fractions and the compound 1 were investigated for antitubercular activity against Mycobacterium tuberculosis H37Ra. Compound 1 showed the activity with IC50 and MIC values at 8.9 and >100 μg/mL. However, the acetone extract of Blainvillea latifolia was inactive against two Gram negative (E. coli, P. flurescence) and two Gram-positive (S. aureus, B. subtilis) bacterial strains. Hence, it was concluded that the extract and the compound 1 are specifically active against MTB and not against bacterial strains. Molecular docking study was performed against crucial mycobacterial target MtInhA to gain an insight into the binding mode and the thermodynamic interactions governing the binding affinity of this molecule.